Market opportunities for African agriculture: an examination of demand-side constraints on agricultural growth - Diao, Xinshen; Dorosh, Paul A.; Rahman, Shaikh Mahfuzur (International Food Policy Research Institute, 2003)
Rapid growth in the agricultural sector is central to any strategy for slashing poverty and hunger on the African continent. Yet investments aimed at increasing agricultural productivity need to be linked to market opportunities if they are not to depress commodity prices and farm incomes. It is widely perceived that high market transaction costs, weak domestic consumer demand, and lack of export possibilities are major constraints on agricultural growth prospects for Africa. But just how severe are these constraints, and what can be done to enhance market opportunities to enable agriculture to become a more powerful engine of growth for the continent? This study addresses these questions. It concludes that non-traditional exports have the fewest constraints and remain the most profitable option for increasing export earnings.....Thus, investments in agriculture and other efforts to promote higher agricultural productivity growth need to be complemented with policies and investments to spur non-agricultural growth. More generally, investments in rural infrastructure can help to maximize positive linkage effects of agricultural growth. Agricultural growth can play a major role in increasing food supply, but sustained increases in incomes and reductions in poverty are likely to require a combination of labor-intensive growth in both agricultural and nonagricultural activities. -- from Authors' Abstract